Bargaining to Achieve Teacher Control in Ontario - Charles, Lawrence; Humphreys, Edward (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
Teachers' aspirations to professionalism are manifested in a desire to control educational decision-making. This research investigates success in achieving control of decision-making under formal bargaining, as defined by The School Boards andTeachers' Collective Negotiations Act, compared to non-formal bargainingused prior to 1975.